2020
DOI: 10.35912/joste.v2i2.539
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility (CSR) practices of financial institution in Bangladesh: the case of United Commercial Bank

Abstract: Purpose: The main purpose of the research is to understand the CSR practices of financial institutions in Bangladesh better. Research methodology: Corporate Social Responsibility (CSR) is concerned with businesses’ interactions with society as a whole. Such CSR operations cover an organisation’s fiscal, legal, ethical, and philanthropic obligations. United Commercial Bank Limited (UCB) has been chosen as the study’s subject. This study is a qualitative research project that used an exploratory research desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…However, Incineration makes a more significant negative contribution to local air quality than landfill. Afrin, Sehreen, Polas, and Sharin (2020) had observed that such effects include cancer among both children and adults, adverse impacts on the respiratory system, heart disease, immune system effects, increased allergies and congenital abnormalities. Some studies, particularly those on cancer, have focused on old rather than modern incinerators.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…However, Incineration makes a more significant negative contribution to local air quality than landfill. Afrin, Sehreen, Polas, and Sharin (2020) had observed that such effects include cancer among both children and adults, adverse impacts on the respiratory system, heart disease, immune system effects, increased allergies and congenital abnormalities. Some studies, particularly those on cancer, have focused on old rather than modern incinerators.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Price is a key factor in customer satisfaction (Hult, Mena, Gonzalez-Perez, Lagerström, & Hult, 2018). In this study, customers are probably price-sensitive, meaning the pricing model impacts brand preference and intention to continue using the service (Afrin, Sehreen, Polas, & Sharin, 2020;Bhattacharjee, Polas, & Rahman, 2018;Widiastiti, Yasa, & Rahanata, 2020). H6: Price Fairness positively and significantly relates to customer satisfaction.…”
Section: Price Fairnessmentioning
confidence: 93%
“…These reviews offer significant insights but have concentrated on a few determinants with less specific future directions. Social and environmental disclosure deals with information on operations, plans, ambitions, and public image in connection with the environmental, employees, customers, and community (Afrin, Sehreen, Polas, & Sharin, 2020;Gray, Javad, Power, & Sinclair, 2001;Suileek & Alshurafat, 2022). Therefore, environmental accounting should provide common disclosure to remove asymmetric and incomplete information.…”
Section: Introductionmentioning
confidence: 99%